Prevalence of Diabetes Mellitus and Diabetic Retinopathy in Persons 50 Years and Above in Katsina State Nigeria: A Population-based Cross-sectional Survey. (2nd September 2020) - Rabiu, Muhammad Mansur; Taryam, Manal O; Muhammad, Nasiru; Oladigbolu, Kehinde; Abdurahman, Halima
ABSTRACT: Purpose: To estimate the prevalence and magnitude of diabetes mellitus and diabetic retinopathy among people with diabetes mellitus in Katsina State. Methods: A population-based cross-sectional study of persons aged 50 years and over in Katsina State Nigeria based on the rapid assessment of avoidable blindness survey plus diabetic retinopathy methodology. The study was conducted in November and December 2018. Results: A total of 2, 653 of the 2, 807 (94.5%) enrolled persons were examined. The unadjusted prevalence of diabetes was 3.3% (95% CI: 2.7–4.1) with females having higher risk of having diabetes than males (OR 1.04; (95% CI 1.00–1.07; P = .03). The age-sex adjusted magnitude of diabetes mellitus is 15, 492 persons in the study population, but 60% of the people are unaware of their disease status. The proportion of people with diabetes mellitus and any retinopathy is 26.2% (95%CI: 14.4–31.6); 15.8% in males and 35.7% in females. The proportion of people with diabetes mellitus with any maculopathy is 12.5% (95% CI: 6.9 − 21.5). The proportion of people with diabetes mellitus having any retinopathy and/or maculopathy is 26.2% while that of a sight-threatening lesion is 7.5%. Conclusion: The burden of diabetes and diabetic retinopathy in the population is lower than national average and elsewhere. However, there is still need to establish a simple cost-effective diabetic retinopathy service for the population as the burden of the problem will only increase with time.